Abnormal Cerebral Blood Flow and Volumetric Brain Morphometry in Patients With Obstructive Sleep Apnea - Xiao, Ping; Hua, Kelei; Chen, Feng; Yin, Yi; Wang, Jurong; Fu, Xiangjun; Yang, Jiasheng; Liu, Qingfeng; Chan, Queenie; Jiang, Guihua (Frontiers in Neuroscience, 2022)
Obstructive sleep apnea (OSA) is a serious breathing disorder, leading to myocardial infarction, high blood pressure, and stroke. Brain morphological changes have been widely reported in patients with OSA. The pathophysiological mechanisms of cerebral blood flow (CBF) changes associated with OSA are not clear. In the study, 20 patients with OSA and 36 healthy controls (HCs) were recruit, and then pseudo-continuous arterial spin labeling (pCASL) and voxel-based morphometry (VBM) methods were utilized to explore blood perfusion and morphological changes in OSA patients. Compared with HCs group, the OSA group showed increased CBF values in the right medial prefrontal cortex (mPFC), left precentral gyrus, right insula, and showed decreased CBF values in the right temporal pole (TP) and the right cerebellum_Crus2. Compared with HCs group, the OSA patients showed decreased gray matter volume (GMV) in the right dorsal lateral prefrontal cortex (DLPFC), right occipital pole, and the vermis. There was no significant increased GMV brain regions found in OSA patients. Pearson correlation analysis showed that the reduced GMV in the right DLPFC and the right occipital pole were both positively correlated with Mini-Mental State Examination (MMSE) (r = 0.755, p < 0.001; r = 0.686, p = 0.002) and Montreal Cognitive Assessment (MoCA) scores (r = 0.716, p = 0.001; r = 0.601, p = 0.008), and the reduced GMV in the right occipital pole was negatively correlated with duration of illness (r = -0.497, p = 0.036). OSA patients have abnormal blood perfusion metabolism and morphological changes in brain regions including frontal lobe and cerebellum, and were closely related with abnormal behavior, psychology, and cognitive function, which play an important role in the pathophysiological mechanism of OSA.